2018
DOI: 10.3389/fgene.2018.00156
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Regulome Variability Along the Organ of Corti: Evidence, Approaches, Challenges, and Perspective

Abstract: The mammalian hearing organ is a regular array of two types of hair cells (HCs) surrounded by six types of supporting cells. Along the tonotopic axis, this conserved radial array of cell types shows longitudinal variations to enhance the tuning properties of basilar membrane. We present the current evidence supporting the hypothesis that quantitative local variations in gene expression profiles are responsible for local cell responses to global gene manipulations. With the advent of next generation sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 173 publications
(226 reference statements)
1
22
0
Order By: Relevance
“…1j, Table S2). As previously reported [29,30], we also quantified the numbers of various cell types of SCs and found that the numbers of IPCs and OPCs were significantly decreased in the apical and middle turns of Foxg1 cKD mice cochleae, respectively (Fig. 1i, j and k), which suggest that the extra HCs might be generated by direct trans-differentiation of SCs.…”
Section: Foxg1 Ckd In Neonatal Mouse Cochlear Scs Led To Significantlsupporting
confidence: 76%
See 1 more Smart Citation
“…1j, Table S2). As previously reported [29,30], we also quantified the numbers of various cell types of SCs and found that the numbers of IPCs and OPCs were significantly decreased in the apical and middle turns of Foxg1 cKD mice cochleae, respectively (Fig. 1i, j and k), which suggest that the extra HCs might be generated by direct trans-differentiation of SCs.…”
Section: Foxg1 Ckd In Neonatal Mouse Cochlear Scs Led To Significantlsupporting
confidence: 76%
“…The up-regulation of canonical Wnt signaling induces the proliferation of sensory precursors in the postnatal mouse cochlea [3,4,[11][12][13][14][15][16][17], while Notch inhibition induces mitotic generation of HCs in the mammalian cochlea via activation of the Wnt pathway [12,14,[18][19][20][21][22][23][24][25]. Also, their effect on differentiation and the generation of HCs is related to important genes such as Atoh1 and Neurog1 [26][27][28][29][30][31][32][33][34]. Foxg1 (formerly called Bf-1) is one of the forkhead box (FOX) family genes, and it plays an important role in neuron development and has been reported to engage in crosstalk with Wnt, Notch, and TGFβ signaling in the brain and eye [35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…High-profile, hearingrelated datasets have been made available in the gEAR even before publication, and links to gEAR as the primary method for accessing datasets are ubiquitous within talks/posters at professional conferences. Additionally, the gEAR has already been used for data dissemination 5,[23][24][25][26][27][28][29][30][31][32][33][34][35] , hypothesis generation [36][37][38][39][40][41][42][43][44] and validation of gene expression 29,30,[45][46][47][48][49][50][51][52][53][54][55][56][57] by numerous publications in the ear field. It has also been referenced by numerous groups as a useful tool [58][59][60][61][62][63][64] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OC-HCs are more susceptible to degeneration after embryonic ablation of afferents whereas vHCs are more robust ( Kersigo and Fritzsch, 2015 ), suggesting that differences in physiological properties include differential sensitivity to various components of the mechanotransduction system. While our understanding of the relative necessity of parts of the mechanosensory channel between the vHCs and OC-HCs is greatly increasing, there is a lack of understanding of both why these differences are necessary for specialization of these different HCs and the gene regulatory networks that drive these differences during development ( Booth et al, 2018 ; Ellwanger et al, 2018 ).…”
Section: Differences Between Vestibular and Cochlear Stereocilia Andmentioning
confidence: 99%